2016
DOI: 10.15517/rbt.v64i1.18235
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical differences along the intestine of Corydoras paleatus (Siluriformes: Callichthyidae)

Abstract: Abstract:The Neotropical catfish Corydoras paleatus is a facultative air-breather and the caudal half of the intestine is involved in gas exchange. In South America, air-breathing fishes are found in tropical or sub-tropical freshwaters where the probability of hypoxia is high. The aim of this study was to characterize by traditional histochemical and lectinhistochemical methods the pattern of carbohydrate in the intestinal mucosa. Intestine samples were taken from 25 healthy adult specimens collected in Bueno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Similar to Tambaqui, the GC distribution of four from the six fishes fall in line with other omnivorous species such as C. paleatus (Plaul et al, 2016), P. fulvidraco (Cao & Wang, 2009) P. antalyae (Çinar & Şenol, 2006), and P. mesopotamicus, of the same family of Tambaqui Serrasalmidae (da Cruz, Moretti, Nordi, Cyrino, & Machado-Neto, 2017), except for A. bimaculatus (Cardoso et al, 2015) and T. obscrus (Hur et al, 2016) that showed assorted distribution of GCs (Table 3).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to Tambaqui, the GC distribution of four from the six fishes fall in line with other omnivorous species such as C. paleatus (Plaul et al, 2016), P. fulvidraco (Cao & Wang, 2009) P. antalyae (Çinar & Şenol, 2006), and P. mesopotamicus, of the same family of Tambaqui Serrasalmidae (da Cruz, Moretti, Nordi, Cyrino, & Machado-Neto, 2017), except for A. bimaculatus (Cardoso et al, 2015) and T. obscrus (Hur et al, 2016) that showed assorted distribution of GCs (Table 3).…”
Section: Discussionsupporting
confidence: 63%
“…Similar to Tambaqui, the GC distribution of four from the six fishes fall in line with other omnivorous species such as C . paleatus (Plaul et al, ), P . fulvidraco (Cao & Wang, ) P .…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar 5 5 mm 1 h in Labeo rohita (Rai et al, 2012). Accumulation of mucus in the wound gap soon after the infliction of wound is significant in the light of the reports that fish skin mucus is associated to play various important functions (Plaul, Barbeito, & Díaz, 2016;Shephard, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Accumulation of mucus in wound gap in 30 min to 2 h has also been reported in the incised wound in the skin of Rita rita (Mittal & Munshi, ); within 1 h in Labeo rohita (Rai et al, ). Accumulation of mucus in the wound gap soon after the infliction of wound is significant in the light of the reports that fish skin mucus is associated to play various important functions (Plaul, Barbeito, & Díaz, ; Shephard, ). Recently, Balasubramanian et al (), Nigam, Kumari, Mittal, and Mittal (), and Kumari, Nigam, Mittal, and Mittal () suggested that skin mucus play an important role in the protection of the fish against microbial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Of each ovary, no less than 15 follicles in which the ZP was evident were observed; among them: preantral, secondary, tertiary, polyovulatory and atretic follicles. The intensities of the different techniques were classified according to the following semi‐quantitative scale: 0, unlabelled; 1, light mark; 2, moderate mark; and 3, strong mark, according to the criterion used in previous works (Barbeito, Ortega, Matiller, Gimeno, & Salvetti, ; Boonzaier, Merwe, Bennett, & Kotze, ; Liquori et al, ; Mastrodonato, Mentino, Liquori, & Ferri, ; Plaul, Barbeito, & Díaz, ), including some carried out in the species under study (Flamini et al, ; Tano de la Hoz, Flamini, & Díaz, ).…”
Section: Methodsmentioning
confidence: 99%